Impact of Parental Health Beliefs on Early Childhood Caries: A Two-Year Longitudinal Study - Yi-Chang Chou; Feng-Shiang Cheng; Shih-Han Weng; Chih-Hao Tseng; Hsiao-Yun Hu; Chieh-Hsing Liu (International Dental Journal)
Introduction and aims: Early childhood caries (ECC) is a widespread chronic condition that significantly affect children’s health and well-being. Although parental psychosocial factors are key to shaping children’s oral health behaviours, few studies have examined the distinct influences of fathers’ vs mothers’ health beliefs. The Health Belief Model (HBM) – which examines health behaviours through perceived susceptibility, severity, benefits, barriers, and self-efficacy – provides a valuable framework for examining these dynamics. This study applied the HBM to investigate the associations between caregiver beliefs, behaviours, and ECC risk, with a focus on differences between fathers and mothers. Methods: We conducted a longitudinal analysis utilizing data from the Taipei Preschool Oral Health Screening Program (2017-2018), including children aged 3-5 years. Eligible participants had complete oral examination records and parental HBM-based questionnaires for 2 consecutive years. Children with incomplete questionnaires were excluded, yielding a final sample of 6902. Generalized estimating equations assessed associations between caregiver oral health beliefs, self-efficacy, perceived barriers, cues to action, behaviours, and ECC risk, stratified by caregiver type (father or mother). Results: Higher parental education, better child oral health behaviours, lower perceived barriers, and greater self-efficacy were significantly correlated with reduced ECC risk. Conversely, higher cues to action were linked to increased ECC risk, indicating a reactive rather than preventive approach. Stratified analyses revealed differing patterns: among fathers, only education and oral health knowledge were significantly protective, whereas among mothers, child oral health behaviours, perceived barriers, and self-efficacy were also significant predictors. Conclusion: Parental psychosocial factors substantially influence ECC risk, with distinct roles for fathers and mothers. These findings highlight the importance of considering caregiver gender in future research and oral health intervention design. Clinical relevance: Family-centred, gender-specific interventions that address caregiver-specific beliefs and behaviours may improve ECC prevention strategies and help reduce oral health disparities in preschool-aged children.